2011
DOI: 10.1182/blood-2010-10-306571
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of immune activation by a novel nuclear factor-kappa B inhibitor in HTLV-I–associated neurologic disease

Abstract: The human T-lymphotropic virus type I (HTLV-I IntroductionInfection with the retrovirus human T-lymphotropic virus type I (HTLV-I) is associated with the development of HTLV-Iassociated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia/lymphoma (ATLL). HAM/TSP is an immune-mediated inflammatory disorder of the central nervous system that leads to progressive neurologic disability in affected individuals. 1 A key mechanism in the pathogenesis of HAM/TSP is considered to be the HTLV-I-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Therefore, bortezomib-induced cytotoxicity cannot be fully attributed to inhibition of canonical NF-κB activity in MM cells (19, 20). Since inhibition of both canonical and non-canonical pathways is required to efficiently block total NF-κB activity, we here characterize the anti-tumor activity of PBS-1086, an inhibitor of both canonical and non-canonical NF-κB pathways (21), in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bortezomib-induced cytotoxicity cannot be fully attributed to inhibition of canonical NF-κB activity in MM cells (19, 20). Since inhibition of both canonical and non-canonical pathways is required to efficiently block total NF-κB activity, we here characterize the anti-tumor activity of PBS-1086, an inhibitor of both canonical and non-canonical NF-κB pathways (21), in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, treatment with IMD-0354 alone suppressed the proliferation of not only ATL cell lines, but also HTLV-I-infected cell lines established by infection in vitro, which express the viral oncoprotein, Tax, suggesting that IMD-0354 could eventually prevent the emergence of leukemic cell clones in asymptomatic carriers, (36) and also be useful in con-trolling NF-jB activity of HTLV-I antigen-expressing cells in human T-cell leukemia virus type I-associated myelopathy/ tropical spastic paraparesis (HAM ⁄ TSP) patients. (37) In conclusion, IMD-0354 effectively suppressed the survival of primary and established ATL cells in vitro and in vivo. These results raise the possibility of small molecularweight IKK inhibitors, such as IMD-0354, as a novel therapeutic agent for ATL treatment.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that PBMCs from HAM/TSP patients showed increased STAT5 activation, as indicated by STAT5 phosphorylation, in short‐term (20 h) culture, which was partially inhibited by Hu‐Mikβ1 . In the current study, we examined pSTAT5 in CD4 + and CD8 + T cells of HVs and HAM/TSP patients using fresh whole blood.…”
Section: Resultsmentioning
confidence: 93%
“…Among the five HAM/TSP patients that demonstrated CD122 saturation, three patients demonstrated sustained saturation of CD122 on NK cells and CD8 + T cells during the Hu‐Mikβ1 treatment period and then lost saturation of CD122 by 6 weeks after the final dose. Importantly, the higher doses of Hu‐Mikβ1 administration provided more inhibitory effects on activated T cell functions of HAM/TSP patients, which are the characteristic features of T cell dysregulation in HAM/TSP patients . In addition, HAM/TSP patients with longer disease duration (such as HAM#5, #6, and #8) seemed to show more effects of Hu‐Mikβ1 on CD122 saturation and inhibition of activated CD8 + T cells compared to HAM/TSP patients with shorter disease duration (such as HAM#7), which might be related to chronic activation and/or expansion of CD8 + T cells in the patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation